2018
DOI: 10.3177/jnsv.64.200
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Alleviates Hepatic Endoplasmic Reticulum Stress under Physiological Conditions

Abstract: Summary Fibroblast growth factor 21 (FGF21), mainly synthesized and secreted from the liver, is an endocrine FGF that regulates glucose and fatty acid metabolism to maintain whole body energy homeostasis. Gene expression of FGF21 was previously reported to be induced by endoplasmic reticulum (ER) stress through activating transcription factor 4 (ATF4). It has been reported that drug-induced ER stress is reduced by overexpression of FGF21. However, the function of endogenous FGF21 under physiological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…When the ERS occurs, one of ERS specific pathway, containing CHOP, is activated, and consequently expression of endogenous FGF21 is upregulated49. Furthermore, intraperitoneal injection of tunicamycin, an endoplasmic reticulum stressor, to normal mice can also induce hepatic FGF21 expression directly50. The same results are also confirmed in the adipocyte45 and H9C2 cardiomyocytes51.…”
Section: Discussionmentioning
confidence: 68%
“…When the ERS occurs, one of ERS specific pathway, containing CHOP, is activated, and consequently expression of endogenous FGF21 is upregulated49. Furthermore, intraperitoneal injection of tunicamycin, an endoplasmic reticulum stressor, to normal mice can also induce hepatic FGF21 expression directly50. The same results are also confirmed in the adipocyte45 and H9C2 cardiomyocytes51.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, serum FGF-21 levels actually increased after glucose ingestion in our study. The predominant role of FGF-21 in the adaptive responses to nutritional and physiological stressors [40] consists of ameliorating postprandial endoplasmic reticulum stress [82] and glucose is the major responsible of inflammatory and oxidative stress postprandial changes [27,28], further suggesting a compensatory homeostatic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 is abundantly expressed in the liver, which is the source of more than 80% of circulating FGF21 [ 23 ]. Recent findings have suggested that intracellular stressors, such as autophagy defects, endoplasmic reticulum stress, calcium imbalance and mitochondrial dysfunction, can induce FGF21 expression [ [24] , [25] , [26] ]. Many chronic diseases are associated with increased intracellular oxidative stress, and FGF21 is considered a novel oxidative stress regulator in humans [ 24 , [27] , [28] , [29] ].…”
Section: Introductionmentioning
confidence: 99%